MIRADA CRÍTICA AL ESTADO SOCIAL DE DERECHO Y LA EFECTIVIZACIÓN DE LOS DERECHOS HUMANOS EN COLOMBIA: “EL INTENTO DE LLEVAR LA PROSPERIDAD A TRAVÉS DEL DESARROLLO” (2016)
To speak of human rights, it is to preach the same “human” but with extension in their actions toward other living and nonliving, own it an atmosphere of harmony consistent with the flowering of the human species. In this context, is the idea of modernity, where more primitive advance towards civilization, underlies the thinking of developing the backward and considered under the global model of organization and classification between developed and developing countries, the result of this dominant economic structure of capitalism and the market, adapting policy instruments and the possibility of realization according to the policies of “development” and thus, the essence of humanity seems to fade and with it the flowering of the human low respect for the dignity, moving to a scenario of reification, to the point that human life becomes a “bare life”, ie, a life of anyone, anything, in which the alien has not been reality of Colombia, with its policy instruments positivization a cluster of rights largely influenced by the neoliberal model, extension material only to a certain elite and where collective struggle emerges as the only solution for the recovery of the human element, without which it is impossible conception as such, that is, the aforementioned value-founding principle of “Dignity”.